A Hybrid ConvLSTM-Based Anomaly Detection Approach for Combating Energy Theft - Gao, Hong-Xin; Kuenzel, Stefanie; Zhang, Xiao-Yu (IEEE transactions on instrumentation and measurement, 2022)
In a conventional power grid, energy theft is difficult to detect due to limited communication and data transition. The smart meter along with big data mining technology leads to significant technological innovation in the field of energy theft detection (ETD). This article proposes a convolutional long short-term memory (ConvLSTM)-based ETD model to identify electricity theft users. In this work, electricity consumption data are reshaped quarterly into a 2-D matrix and used as the sequential input to the ConvLSTM. The convolutional neural network (CNN) embedded into the long short-term memory (LSTM) can better learn the features of the data on different quarters, months, weeks, and days. Besides, the proposed model incorporates batch normalization. This technique allows the proposed ETD model to support raw format electricity consumption data input, reducing training time and increasing the efficiency of model deployment. The result of the case study shows that the proposed ConvLSTM model exhibits good robustness. It outperforms the multilayer perceptron (MLP) and CNN-LSTM in terms of performance metrics and model generalization capability. Moreover, the result also demonstrates that K -fold cross validation can improve the ETD prediction accuracy.